1984
DOI: 10.1093/nar/12.23.9025
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure at the 44D larval cuticle gene locus inDrosophila: the effect of a transposable element insertion

Abstract: The chromatin structure of the larval cuticle gene cluster at 44D was characterized in embryos from wild-type (Oregon R) and a variant line (2/3) of Dophi melanogaster. A major DNase I hypersensitive (DH) site was found between genes II and III in the chromatin, in a position 5' to the transcriptional start of the genes in the cluster. The introduction of a 7.3 kilobase transposable element into the cluster in the 2/3 variant enhanced the sensitivity of the major site in 2/3 chromatin but had no other effect u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…These hypersensitive sites have been observed adjacent to genes encoding heat-shock proteins (2, 3), 3-globin (4-6), histones (7), a Drosophila glue protein (8) and larval cuticle gene cluster (9), and on SV40 minichromosomes (10). Furthermore, these sites have been associated with many different sequences which are involved in gene expression and frequently their appearance has been correlated with developmental and tissue-specific gene activation (4-6, 8, the gene is expressed (13,17).…”
Section: Introductionmentioning
confidence: 99%
“…These hypersensitive sites have been observed adjacent to genes encoding heat-shock proteins (2, 3), 3-globin (4-6), histones (7), a Drosophila glue protein (8) and larval cuticle gene cluster (9), and on SV40 minichromosomes (10). Furthermore, these sites have been associated with many different sequences which are involved in gene expression and frequently their appearance has been correlated with developmental and tissue-specific gene activation (4-6, 8, the gene is expressed (13,17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that active or inducible genes are highly sensitive to digestion with DNase I (Eissenberg et al, 1985), that enhancer sequences are often associated with DNase I-hypersensitive (DH) sites (Jongstra et al, 1983;Thompson and Fan, 1985), and that insertion of transposable genetic elements sometimes modifies the DH sites of host genomes or creates new DH sites (McGinnis et al, 1983;Eissenberg et al, 1984;Eissenberg and Elgin, 1987). To explore the mechanism of positive regulation of G6PD by the core sequence, the DH sites in the 5' region of G6PD gene were examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the DH sites within the hobo seem to influence transcription initiation, since multiple new transcription start sites were found 5' to the normal site. Eissenberg et al (1984) reported that the sensitivity of the major DH site located between larval cuticle protein genes//and III was enhanced by the insertion of the H.M.S. Beagle element into the 5' region of the IIIgene and that the element itself had a DH site within each of the direct terminal repeats, but expression of the III gene was suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…The site in the right-hand P-element end was not as well resolved; we could only place it with certainty within the last 100 base pairs of the P-element. instances in which multiple transformation events were identified, each tranduced locus when examined separately was found to be active (16,25 (27) and of the copia-like transposable element, HMS Beagle, in D. melanogaster (4) suggests that this specialized chromatin structure is a general feature of the terminal regions of transposable sequences in eucaryotes.…”
mentioning
confidence: 99%